Modeling Diet-Induced NAFLD and NASH in Rats: A Comprehensive Review - Carreres, Lydie (Biomedicines, 2021)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease, characterized by hepatic steatosis without any alcohol abuse. As the prevalence of NAFLD is rapidly increasing worldwide, important research activity is being dedicated to deciphering the underlying molecular mechanisms in order to define new therapeutic targets. To investigate these pathways and validate preclinical study, reliable, simple and reproducible tools are needed. For that purpose, animal models, more precisely, diet-induced NAFLD and nonalcoholic steatohepatitis (NASH) models, were developed to mimic the human disease. In this review, we focus on rat models, especially in the current investigation of the establishment of the dietary model of NAFLD and NASH in this species, compiling the different dietary compositions and their impact on histological outcomes and metabolic injuries, as well as external factors influencing the course of liver pathogenesis.